Risk of Bleeding Associated With Nonsteroidal Anti‐inflammatory Drug Use in Patients Exposed to Antithrombotic Therapy: A Case‐Crossover Study. (5th January 2022) - Paternoster, Morgane; Steichen, Olivier; Lapeyre‐Mestre, Maryse; Blanchon, Thierry; Rossignol, Louise; Vilcu, Ana‐Maria; Launay, Titouan; Sarazin, Marianne; Bagheri, Haleh; Conte, Cécile; Turbelin, Clément; Hanslik, Thomas; et al.
Abstract: Concomitant nonsteroidal anti‐inflammatory drug (NSAIDs) and antithrombotic drug use is associated with an increased risk of bleeding, mainly gastrointestinal. The goal of this study was to quantify the transient increase in the risk of hospitalization for bleeding associated with NSAID use in patients treated with antiplatelet agents or anticoagulants. We performed a unidirectional case‐crossover study using the EGB (Échantillon généraliste de bénéficiaires), a permanent random sample of the French nationwide health database. Patients receiving antithrombotic therapy and hospitalized for bleeding between 2009 and 2017 were included. We compared their NSAID exposure during a 15‐day hazard window immediately before hospital admission to 3 earlier 15‐day control windows. The risk of hospitalization for bleeding associated with the recent use of NSAIDs was estimated using conditional logistic regression to estimate odds ratios (ORs). During the study period, 33 patients treated with anticoagulants and 253 treated with antiplatelet agents received NSAIDs and were included in the case‐crossover analysis. We found an increased risk of hospitalization for gastrointestinal bleeding after exposure to NSAIDs, with an adjusted OR of 3.59 (95%CI, 1.58‐8.17) in patients receiving anticoagulant therapy and 1.44 (95%CI, 1.07‐1.94) in patients receiving antiplatelet therapy. The risk of nongastrointestinal bleeding was also increased after exposure to NSAIDs with an adjusted OR of 2.72 (95%CI, 1.23‐6.04) in patients exposed to anticoagulant therapy. The risk of gastrointestinal and nongastrointestinal bleeding increases after NSAID use in patients treated with anticoagulants, while the risk of gastrointestinal bleeding increases, but to a lesser extent in those treated with antiplatelets.